Medicinal plants used for treatment of wounds and skin infections: assessment of wound healing and antimicrobial properties of Mallotus oppositifolius and Momordica charantia - Christian Agyare; Ebenezer Amuah; Martin Adarkwa-Yiadom; Samuel Osei-Asante; Paul Poku Sampane Ossei (International Journal of Phytomedicine, 2014)
Mallotus oppositifolius and Momordica. charantia are two medicinal plants used in folk medicine for the treatment of skin infections and disorders, wounds, peptic ulcer, fever, piles and parasitic infections. The aim of the study was to determine the antimicrobial, antioxidant and wound healing properties of the methanol leaf extracts of M. oppositifolius and M. charantia. The two plants extracts were screened for their phytochemical composition and their antimicrobial activity was also determined against three gram-positive, two gram-negative bacteria and a fungus. The antioxidant or free radical scavenging activity of the methanol leaf extracts was also determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH). The wound healing activity of the extracts was determined by the excision wound model in rats. The results indicated that both extracts contain tannins, alkaloids, flavonoids and glycosides and M. charantia contains saponins. The two extracts exhibited activity against all the test organisms. MICs of the methanol leaf extract of M. oppositifolius was between 0.01 to 3.75 mg/mL and that of M. charantia was between 1.88 to 7.5 mg/mL. The IC50 of methanol leaf extracts of M. oppositifolius and M. charantia were 16.11 and 7.09 µg/mL respectively. The wound contraction rate was significant (p<0.05) for both extracts of M. oppositifolius and M. charantia on the 11th day compared to the untreated group. The extracts exhibited high antimicrobial and antioxidant activities and increased fibrosis and collagenation in the wound tissues and the rate of wound closure compared with the untreated wounds at the late phase of the wound healing process.